Universities in the context of social history: from “education of culture” to formation of creative intellectual environments - Andrey L. Andreev (Высшее образование в России, 2022)
The article considers some correlations between the idea of the university and its real social functions. It also suggests some assumptions concerning the evolution of the universities in future.